Destruction of OPA from munitions demilitarization in supercritical water oxidation: Kinetics of total organic carbon disappearance - Veriansyah, Bambang; Kim, Jae-Duck; Lee, Jong-Chol; Hong, Deasik (TAYLOR & FRANCIS INC, 2006)
The destruction of OPA from munitions demilitarization has been accomplished in supercritical water oxidation (SCWO) with oxygen as oxidant in an isothermal continuous-flow reactor. The experiments were conducted at a temperature of 689 887 K and a fixed pressure of 25 MPa, with a residence time that ranged from 7 s to 14 s. The destruction efficiency was measured by total organic carbon (TOC) conversion. At the reaction condition, the initial TOC concentrations of OPA were varied from 1.41 mmol/L to 19.57 mmol/L and the oxygen concentrations were varied from 15.03 mmol/L to 81.85 mmol/L. Experimental data showed that all the TOC conversions were > 80% under the above experimental conditions. The kinetics of TOC disappearance, which is essential for the design, optimization, and control of reliable commercial SCWO reactor was developed by taking into account the dependence of the oxidant and TOC concentration on the reaction rate. A global TOC disappearance rates expression was regressed from the data of 38 experiments, to a 95% confidence level. The resulting activation energy was determined to be 44.01 +/- 1.52 kJ/mol, and the pre-exponential factor was (1.67 +/- 0.45) x 10(2) L(1.14) mmol(-0.14) s(-1). The reaction orders for the TOC and the oxidant were 0.98 +/- 0.01 and 0.16 +/- 0.02, respectively.